2022
DOI: 10.3390/ijms231911860
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Koumine on Growth Performance, Intestinal Morphology, Microbiota, and Intestinal Transcriptional Responses of Cyprinus carpio

Abstract: Gelsemium elegans Benth. (GEB) is a traditional medicinal plant in China, and acts as a growth promoter in pigs and goats. Koumine (KM) is the most abundant alkaloid in GEB and produces analgesic, anti-cancer, and immunomodulatory effects. KM can be used as an aquatic immune stimulant, but its growth-promoting effects and transcriptional mechanisms have not been investigated. Diets containing KM at 0, 0.2, 2, and 20 mg/kg were fed to Cyprinus carpio for 71 days to investigate its effects on growth performance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Similarly, koumine pretreatment reduced the MDA content significantly and inhibited apoptosis in intestinal porcine enterocytes induced with H 2 O 2 [34]. Dietary koumine also reduced MDA in the intestine of common carp [35].…”
Section: Itemmentioning
confidence: 84%
“…Similarly, koumine pretreatment reduced the MDA content significantly and inhibited apoptosis in intestinal porcine enterocytes induced with H 2 O 2 [34]. Dietary koumine also reduced MDA in the intestine of common carp [35].…”
Section: Itemmentioning
confidence: 84%
“…CYP1A1 is a monooxygenase whose activation can lead to the overproduction of reactive oxygen species (ROS) and cause oxidative stress, which is a critical factor in hepatotoxicity [ 10 ]. Several reports have shown that AHRs are associated with pyroptosis and that the pyroptosis pathway is inhibited when AHRs or CYP1A1 is inhibited [ 30 , 31 ]. CYP1A1 is the key metabolic enzyme and target in many liver diseases, such as drug-induced liver injury and non-alcoholic fatty liver disease [ 9 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Koumine (KM), derived from the stem and leaves of Gelsemium elegans (Gardner & Champ.) Benth., has significant anti-inflammatory effects antitumor, antioxidant, immunomodulatory and hepatoprotective effects ( Wang et al, 2022 ; Que et al, 2023 ). Its immunomodulatory effect on rats with NAFLD has been demonstrated in recent years.…”
Section: Role Of Natural Products and Their Extracts In Fatty Liver D...mentioning
confidence: 99%